Pharmacokinetic Assessment of Staphylococcal Phage K Following Parenteral and Intra-articular Administration in Rabbits - Totten, Katherine M.C.; Cunningham, Scott A.; Gades, Naomi M.; Etzioni, Athema; Patel, Robin (Frontiers in Pharmacology, 2022)
The therapeutic value of phage as an alternative to antibiotics for treatment of bacterial infections is being considered in the wake of mounting antibiotic resistance. In this study, the pharmacokinetic properties of Staphylococcus aureus phage K following intravenous and intra-articular administration was investigated in a rabbit model. Using a traditional plaque assay and a novel quantitative PCR assay to measure phage levels in specimens over time, it was found that intra-articularly administered phage enters the systemic circulation; that phages may be detected in synovial fluid up to 24 hours following intra-articular, but not intravenous, administration; and that qPCR-based enumeration is generally more sensitive than plaque enumeration, with fair to moderate correlation between the two methods. Findings presented should inform design of phage therapy experiments as well as therapeutic drug monitoring in preclinical and human phage studies.